Imaging Assessment of Endothelial Function: An Index of Cardiovascular Health - Minhas, Anum S.; Goerlich, Erin; Corretti, Mary C.; Arbab-Zadeh, Armin; Kelle, Sebastian; Leucker, Thorsten; Lerman, Amir; Hays, Allison G. (Frontiers in Cardiovascular Medicine, 2022)
Endothelial dysfunction is a key early mechanism in a variety of cardiovascular diseases and can be observed in larger conduit arteries as well as smaller resistance vessels (microvascular dysfunction). The presence of endothelial dysfunction is a strong prognosticator for cardiovascular events and mortality, and assessment of endothelial function can aid in selecting therapies and testing their response. While the gold standard method of measuring coronary endothelial function remains invasive angiography, several non-invasive imaging techniques have emerged for investigating both coronary and peripheral endothelial function. In this review, we will explore and summarize the current invasive and non-invasive modalities available for endothelial function assessment for clinical and research use, and discuss the strengths, limitations and future applications of each technique.